Food Insecurity in Housefold Level with Stunting During The Covid-19 Pandemic - Adillah Imansari; Ashyfa Restu Wulandari; Devi Sunista; Herma Jafika; Rutni Tomeys; Sarini (Journal of sciences and health, 2022)
Baground: Food insecurity at the household level occurs when the household is unable to get enough food to live a healthy and active life. The Covid-19 pandemic has an impact on society in terms of getting food which will have an impact on nutritional problems including stunting. The purpose of this study was to analyze the relationship between food insecurity at the household level and stunting during the Covid-19 pandemic. Method: The design of this study was cross sectional with an observational approach and a quantitative study. The research sample was 55 households obtained by purposive sampling using inclusion criteria (respondents' willingness to be a sample) and exclusion (not local people as evidenced by identity cards). The method of collecting research data was using a questionnaire to record characteristics (age and gender) and a food insecurity questionnaire using the Housefold Food Insecurity Access Scale with a total of 9 questions. Data analysis used univariate analysis, namely frequency distribution and bivariate analysis used chi-square to see the relationship between food insecurity and stunting. Results: The results showed that there was no significant relationship (p>0.005) the level of food insecurity in the household with the incidence of stunting. The age group that has a lot of stunting under five is the age group >24 months (60.6%) with the most stunting sex being girl (55.9%) with the category of severe food insecurity (46.2%). Conclusions: There is no significant relationship between the level of food insecurity in the household and the incidence of stunting. There is indicate that the Covid-19 pandemic situation has an impact on changes in consumption patterns which may be related to the level of food insecurity in the household. Therefore, there is a need for further research with the addition of variables for community food consumption during the Covid-19 pandemic and income in order to add explanations about food insecurity at the household level. Keywords:Food insecurity, stunting, Covid-19 pandemic